Pengaruh Pengetahuan Karyawan Bagian Akuntansi, Partisipasi Manajemen dan Pemanfaatan Teknologi Informasi Terhadap Efektivitas Sistem Informasi Akuntansi (Studi Pada PT Perkebunan Nusantara IX, PG. Mojo, Sragen) - Efendi, Taufik, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
Effectiveness of the accounting information system is a success achieved by the accounting information system to produce timely, accurate, and reliable. This study aimed to determine the effect of accounting employee's knowledge, management participation, and the utilization of information technology of the effectiveness of accounting information systems. The research was conducted at the Sugar Factory (PG). Mojo, Sragen. Samples were taken by purposive sampling technique as much as 37 accountants of PG. Mojo, Sragen. Analysis using multiple linear regression analysis. Research results showed accounting employee's knowledge, management participation, and the utilization of information technology positive and significant impact on the effectiveness of accounting information systems (AIS).